Avaliação dos resultados imediatos da prostatectomia radical por via robótica realizada em 849 pacientes com câncer de próstata - Pablo Almeida Melo (2024)
Radical prostatectomy is widely regarded as the gold standard for the treatment of localized prostate cancer. The robotic approach has become the preferred technique due to its potential to improve oncological and functional outcomes. Despite the increase in robotic radical prostatectomies (RRP) in Brazil, there is a paucity of robust studies evaluating this surgical modality comprehensively. Objectives: The study aims to assess the oncological aspects of the disease, surgical indications, and initial surgical outcomes, with a particular focus on the learning curve associated with the procedure. Methods: A retrospective cohort study was conducted involving 849 patients who underwent robotic prostatectomy performed by multiple surgeons, with one surgeon responsible for the majority of the cases. Sociodemographic and clinical data were collected prospectively using standardized questionnaires. The study evaluated the oncological outcomes of the surgery and immediate peri- and postoperative complications. Results: The majority of patients had medium-sized prostates (mean 41.2 grams), with early-stage disease (59.3%). Notably, 92.7% of patients underwent pre-biopsy prostate MRI. Robotic radical prostatectomy demonstrated a low morbidity rate (2%) and no mortality. The surgeon with the highest case volume exhibited superior operative efficiency, including shorter operative times, reduced bleeding rates, and decreased hospitalization durations. Prior experience with laparoscopic radical prostatectomy did not confer a significant clinical outcome advantage. Conclusions: Robotic radical prostatectomy is a safe and effective treatment for localized prostate cancer, underscoring the critical role of surgeon experience in optimizing clinical outcomes.